Acquisitions may add value to resource companies - Bartrop, Stephen Bruce (Curtin University, 2010)
Resource acquisitions have added value to resource companies over the past two decades. This stems from the results of this research which has analysed 30 transactions and further reviewed 22 transactions with a total value A$240 billion. However, this figure is dominated by the 1997 BHP Billiton bid for Rio Tinto and if this attempted takeover is excluded from the list, the total value of the transactions analysed is A$60 billion.The consolidation has occurred in three waves since the early 1990s. These periods are: • First, a period starting in 1995 and ending in 2000; it included the end of the 1992-1996 bull run, the Asian Crisis and a period known as the 1998-2000 bull run and ending during the start of the Tech Boom drift, • Secondly, a period between 2002 and 2004 which combines the waning stages of the Tech Boom drift and the commencement of the 2002-2008 Resources Boom, and, • Thirdly, in a more recent period from 2006 to near the end of the 2002-2008 resources boom.Each of these periods has different characteristics but overall there is a broad trend of foreign bidders acquiring Australian companies during weaker markets except during the 2002-2008 Resources Boom.Cumulative abnormal returns (CAR) for both bidders and targets have been estimated using an adapted market model for event analysis. It draws on the strong correlation of absolute resource share with commodity prices.Friendly transactions offer target shareholders a lower final offer price premia to the 30-day average target share price prior to the announcement (dual listing – 17.8 per cent, mergers – 12.9 per cent) and compares to traditional takeovers which average 48.7 per cent. In traditional takeovers the initial offer to 30-day average premia was 37.2 per cent but increases to the final offer to 30-day average premia of 48.7 per cent mostly reflecting the impact of competitive bidding. Average increases in the final offer prices in non-competitive bidding were 16.6 per cent.While both scrip and cash bids offered similar premia to target shareholders, foreign scrip on average offer a 20 per cent higher premia. Elsewhere, there were no material differences between the premia offered in hostile compared to non-hostile takeovers.Bidders offering a 35 per cent premium (whether cash or scrip) to target shareholders are expected to create CAR for the target shareholders at around 24 per cent on the bid announcement. If the bid involves foreign scrip, the premium needs to be raised by 30 per cent but then the CAR for target shareholders will be slightly lower than non-foreign scrip bids at 22.9 per cent. If, however, the bidder can structure a merger the premium can reduce to zero in a ‘merger of equals’.Overall, the negative bidder CAR during the event window is more than offset by positive CAR during the post-event window, leading to a net positive CAR for acquirers of an average of 7.1 per cent. The positive net CAR for acquirers using scrip bids is 11.3 per cent; it falls to 3.5 per cent for bidders using cash offers.In the alternative investment of exploration there are attractive probability weighted exploration returns but these are dampened by the high levels of expenditure required to achieve satisfactory levels of certainty. This will continue to undermine the investment appeal of junior explorers while greenfield exploration will become solely the domain of the majors.